Istishab (Presumption of Continuity) in Islamic Law: A Comparative Study with Western Legal Principles - Dr. Syed Ameer Hassan, (Dialogue Social Science Review (DSSR), 2025)
Istishab, translated as the "presumption of continuity," is one of the recognized subsidiary sources of Islamic law, employed particularly in the absence of direct evidence. It rests on the principle that a previously established fact is presumed to continue until proven otherwise. This paper examines Istishab from the perspective of various Islamic legal schools, its practical application in matters such as contracts, marriage, and property, and its philosophical foundations in Shari‘ah and rational evidence. The study also compares Istishab with analogous doctrines in Western legal systems, such as the presumption of innocence, continuity of possession, and estoppel, highlighting similarities and differences in epistemic reasoning and evidentiary standards.